Platinum-group element systematics in the North Atlantic Igneous Province: New insights from Northern Irish and Irish magmatism - Anna O. Morrison; Michael J. Stock; Mark R. Cooper; Jens C.Ø. Andersen; Hannah S.R. Hughes; Elliot J. Carter; Jack Beckwith; Iain McDonald; Andrew C. Kerr; Paul Mohr (Lithos, 2026)

Drivers of roe deer use in fragmented forest landscapes; implications for current and future management in the context of policy driven forest expansion - Saudamini Venkatesan; Benjamin M. Marshall; Mark S. Greener; Anna Kinghorn; Isla Sligo-Young; Richard Hassall; Robin Gill; Ben McKeown; Jeanette Hall; Roman Biek; Lucy Gilbert; Thomas A. Morrison; et al. (Forest Ecology and Management, 2026)

Public health risks from potable water supply disruptions during drought in high-income countries: A scoping review and policy implications for the United Kingdom - Daniel Mark Blake; Joanna Orr; Kirsty Morrison; Anh Tran; Paul Christopher Coleman; Grace Anne Turner; Lauren Hands; Katya Brooks (International Journal of Hygiene and Environmental Health, 2026)

Correction: Reducing herbicide leaching by split-dose applications in organomineral and mineral soils - Shane Scannell; Mark G. Healy; John McGinley; Paraic C. Ryan; Per-Erik Mellander; Liam Morrison; Jenny Harmon O’Driscoll; Alma Siggins (Environment, Development and Sustainability, 2026)

Reducing herbicide leaching by split-dose applications in organomineral and mineral soils - Shane Scannell; Mark G. Healy; John McGinley; Paraic C. Ryan; Per-Erik Mellander; Liam Morrison; Jenny Harmon O’Driscoll; Alma Siggins (Environment, Development and Sustainability, 2026)

Integrating approaches and regulations to address plastic pollution: Spotlighting nanosized particles - Sara Novak; Mark Morrison; Rudolf Reuther; Lesley Tobin de Fuentes; Veno Kononenko; Damjana Drobne (NanoImpact, 2026)

Finding the Best Nursery: How Habitat Features Shape Juvenile Snapper ( Chrysophrys auratus ) Density - Jessica L. Campbell; Richard B. Taylor; Mark A. Morrison (New Zealand Journal of Marine and Freshwater Research, 2026)
This study examines habitat preferences of juvenile Australasian snapper ( Chrysophrys auratus ) in northeastern New Zealand, analysing data from 113 stations across structured and unstructured habitats. We investigated how juvenile snapper densities were influenced by environmental factors, including prey availability and physical habitat features. Seagrass supported significantly higher snapper densities than all other habitats, with mean densities more than 80 times greater than non‐seagrass habitats, reinforcing its role as a key nursery habitat. Regression analyses identified seagrass presence as the strongest predictor of density, with benthic productivity and plankton flux also weakly correlated when considering all habitats together. In non‐seagrass environments, there were weak trends for densities to be higher in shallow water and in the presence of burrows. Current speed also appeared to play a role, potentially modifying prey availability and interacting with habitat structure. These findings provide new insights into why seagrass meadows are particularly beneficial for juvenile snapper, reinforcing the need for targeted conservation and restoration efforts to sustain nursery habitats and support snapper populations.

Seagrass Gains: Faster Growth, Better Condition, Less Effort for Juvenile Snapper ( Chrysophrys auratus ) - Jessica L. Campbell; Christine Stewart; Mark A. Morrison (New Zealand Journal of Marine and Freshwater Research, 2026)
Seagrass habitats are widely recognised as key nursery areas for juvenile fish, yet their specific role in supporting growth and condition remains incompletely understood. This study investigates the diet, growth and condition of juvenile (0+) snapper ( Chrysophrys auratus ) across multiple habitats in the Hauraki Gulf and northeastern New Zealand, with a focus on seagrass meadows. A total of 416 snapper were analysed for condition and growth, while diet composition was assessed from 425 gut samples. Results indicate that snapper within seagrass habitats exhibited significantly higher condition and faster growth rates than those in other habitats. However, contrary to expectations, gut fullness was lower in seagrass beds than in non‐seagrass habitats, despite higher prey availability in seagrass meadows. While diet varied among habitat types, no significant differences were detected between seagrass and non‐seagrass habitats. These findings suggest that the advantages conferred by seagrass are not directly linked to food intake but may result from reduced energetic costs associated with shelter from currents, improved foraging efficiency, or lower predation stress. The study highlights the vital role of seagrass meadows in supporting juvenile snapper populations and emphasises the need for conservation and restoration, particularly in areas where these habitats have been lost.

Shallow estuarine reef as nursery habitat for Australasian snapper ( Chrysophrys auratus ) - Jessica L. Campbell; Mark A. Morrison; Richard B. Taylor (New Zealand Journal of Marine and Freshwater Research, 2025)
Estuaries are important recruitment sites for many fish species, with structurally‐complex habitats such as subtidal seagrass beds on soft sediments particularly valuable due to their provision of food and shelter. Soft sediments dominate most estuaries, but where hard‐bottom reefs are present they have the potential to act as nursery habitats for juvenile fish. We document recruitment of juvenile Australasian snapper ( Chrysophrys auratus ) to a shallow linear sandstone reef in Whangateau Harbour, a small estuary in north‐eastern New Zealand. Up to several hundred 0 + juveniles (∼20–70 mm fork length) were present on the reef during early summer to mid‐late autumn each year from 2018 to 2021. Numbers were consistently highest at the seaward end of the reef, facing into incoming tidal currents, and lowest in the deeper central part of the reef, where larger, potentially cannibalistic, snapper were common. Juveniles disappeared from the reef fairly abruptly at the end of each season, with departure in at least two of the years appearing to follow a sudden decrease in water temperature rather than being associated with body size or absolute temperature. Although relatively small in area, estuarine reefs may be increasingly important nursery habitats in the future given the widespread loss of subtidal seagrass beds.

Ambient environmental conditions and active outdoor play in the context of climate change: A systematic review and meta-synthesis - Eun-Young Lee; Seiyeong Park; Yeong-Bae Kim; Henry Liu; Priya Mistry; Kevin Nguyen; Yeonjae Oh; Maeghan E. James; Steven Lâm; Louise de Lannoy; Richard Larouche; Taru Manyanga; et al. (Environmental Research, 2025)

Clarifying the role of the resist–accept–direct framework in supporting resource management planning processes - Gregor W. Schuurman; Wylie Carr; Cat Hawkins Hoffman; David J. Lawrence; Brian W. Miller; Erik A. Beever; Jean Brennan; Katherine R. Clifford; Scott Covington; Shelley D. Crausbay; Amanda E. Cravens; John Gross; et al. (Conservation Biology, 2025)

Prenatal PFAS exposures and cardiometabolic health in middle childhood in the MIREC cohort - Alan J. Fossa; Amber M. Hall; George D. Papandonatos; Tye E. Arbuckle; Jillian Ashley-Martin; Michael M. Borghese; Jenny Bruin; Aimin Chen; Mandy Fisher; John E. Krzeczkowski; Bruce P. Lanphear; Amanda J. MacFarlane; et al. (Environmental Research, 2025)

Classification of direct threats to the conservation of ecosystems and species 4.0 - Nick Salafsky; Claire Relton; Bruce E. Young; Philippe Lamarre; Monika Böhm; Maxime Chénier; Erica Cochrane; Mark Dionne; Kevin K. He; Craig Hilton‐Taylor; Charles Latrémouille; John Morrison; et al. (Conservation Biology, 2025)
Identifying and assessing the magnitude of direct threats to ecosystems and species are critical steps to prioritizing, planning, implementing, and assessing conservation actions. Just as medical clinicians and researchers need a standard way to talk about human diseases, conservation practitioners and scientists need a common and comprehensive language to talk about the threats they are facing to facilitate joint action, evaluation, and learning. To meet this need, in 2008 the IUCN Species Survival Commission and the Conservation Measures Partnership produced the first version of a common threats classification with the understanding that it would be periodically updated to take into account new information and learning. We present version 4.0 of this classification. For this latest update, we reviewed existing versions and derivatives of the original classification, over 1000 citations of the classification, threats data from over 2900 real‐world conservation projects, and comments from many users. Based on our findings, we made changes to the threats classification scheme, including addition of a level 0 threat class, refinement of levels 1 and 2 threat categories, and addition of the threat “Fencing & walls” to level 2. Also added were level 3 threat types and modifiers that provide a more detailed description of different types of direct threats and thus allow users to fine‐tune analyses and actions. The update also clarifies how to treat various stressors, including natural disaster events and climate change. As a result of these changes, we revised the formal definition of direct threats. They include human actions that are the direct cause of ecosystem or species‐population degradation and loss, such as agriculture, transport, natural resource use, and ecosystem management. They also include ultimate stressors in natural systems whose dynamics have been altered by the effects of current or historical human actions, such as invasive or problematic native species, pollution, natural disasters, and climate change.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Seasonal Variability of Golden Tides (Pylaiella littoralis, Phaeophyceae) and Nutrient Dynamics in a Potentially Eutrophic Intertidal Estuary - Sara Haro; Ricardo Bermejo; Mark G. Healy; Kay Knöeller; Owen Fenton; Svenja Heesch; Liam Morrison (Journal of Marine Science and Engineering, 2024)
Understanding macroalgal bloom development is crucial for managing eutrophication and protecting estuarine ecosystems. In this study, brown macroalgal blooms (i.e., golden tides) were identified in a potentially eutrophic temperate estuary (NW Ireland). Pylaiella littoralis (Phaeophyceae, Ectocarpales) was monitored at low tide over seven sampling occasions between June 2016 and August 2017. In situ biomass, tissue nutrients (nitrogen (N) and phosphorus (P)), and isotopic signature (δ15N contents) were measured, and relations with environmental drivers were explored. Difference Vegetation Index (NDVI) values from Sentinel-2 satellite imagery were used to assess the spatiotemporal dynamics of P. littoralis biomass (2016–2022). The results indicated that NDVI attributed to golden tides were lowest in 2022, during summer (coinciding with high temperatures and high rainfall) and at the lower shore on the right margin of an entering river. The highest tissue P content was recorded in April 2017, coinciding with in situ biomass peaks (spring–early summer), suggesting elevated P demand. Tissue N content (>2%) and N:P ratios (10–30) indicated occasional P limitation but no N limitation. δ15N data were very low and it was not possible to identify any primary N source. These findings highlight the importance of nutrient management in mitigating golden tides, addressing eutrophication, and preserving estuarine ecosystems.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Governance of advanced materials: Shaping a safe and sustainable future - Monique Groenewold; Eric A.J. Bleeker; Cornelle W. Noorlander; Adriënne J.A.M. Sips; Margriet van der Zee; Robert J. Aitken; James H. Baker; Martine I. Bakker; Evert A. Bouman; Shareen H. Doak; Damjana Drobne; Verónica I. Dumit; et al. (NanoImpact, 2024)

Influence of the Keystone Grazer, Sesarma reticulatum, on the Hydrology and Organic Matter Cycling in Salt Marshes of the Southeastern USA - Elise S. Morrison; Thomas S. Bianchi; William F. Kenney; Mark Brenner; Kimberly Prince; Sydney Williams; Collin Ortals; Orlando Cordero; Sinéad M. Crotty; Christine Angelini (Estuaries and Coasts, 2024)
In salt marshes of the Southeastern USA, purple marsh crabs ( Sesarma reticulatum ), hereafter Sesarma , aggregate in grazing and burrowing fronts at the heads of tidal creeks, accelerating creek incision into marsh platforms. We explored the effects of this keystone grazer and sediment engineer on salt marsh sediment accumulation, hydrology, and carbon (C) and nitrogen (N) turnover using radionuclides ( 210 Pb and 7 Be), total hydrolyzable amino acids (THAA), and C and N stable isotopes (δ 13 C and δ 15 N) in sediment from paired Sesarma -grazed and un-grazed creeks. Sesarma -grazed-creek sediments exhibited greater bioturbation and tidal inundation compared to sediments in un-grazed creeks, as indicated by larger 210 Pb and 7 Be inventories. Total organic carbon (TOC) to total nitrogen (TN) weight ratios (C:N) were higher and δ 15 N values were lower in grazed-creek sediments than in un-grazed-creek sediments, suggesting Sesarma remove and assimilate N in their tissues, and excrete N with lower δ 15 N values into sediments. In support of this inference, the percent total carbon (TC) and percent TOC declined by nearly half, percent TN decreased by ~ 80%, and the C:N ratio exhibited a ~ threefold increase between Sesarma fore-gut and hind-gut contents. An estimated 91% of Sesarma ’s diet was derived from Spartina alterniflora, the region’s dominant salt marsh plant. We found that, as Sesarma grazing fronts progress across marsh landscapes, they enhance the decay of Spartina- derived organic matter and prolong marsh tidal inundation. These findings highlight the need to better account for the effects of keystone grazers and sediment engineers, like Sesarma , in estimates of the stability and size of blue C stores in coastal wetlands.

Field assessment of coconut-based activated carbon systems for the treatment of herbicide contamination - John McGinley; Mark G. Healy; Shane Scannell; Paraic C. Ryan; Jenny Harmon O'Driscoll; Per-Erik Mellander; Liam Morrison; Alma Siggins (Chemosphere, 2024)

Determining the response of riparian vegetation and river morphology to drought using Google Earth Engine and machine learning - Smriti Chaulagain; Mark C. Stone; Ryan R. Morrison; Liping Yang; Julie Coonrod; Noelani E. Villa (Journal of Arid Environments, 2023)

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Kinetic model of PFAS removal by semi-batch foam fractionation and validation by experimental data for K-PFOS - Jianlong Wang; Robert K. Niven; Anthony Morrison; Scott P. Wilson; Vladimir Strezov; Mark P. Taylor (Science of The Total Environment, 2023)

Analytical method interferences for perfluoropentanoic acid (PFPeA) and perfluorobutanoic acid (PFBA) in biological and environmental samples - Jacqueline Bangma; James McCord; Nathan Giffard; Kate Buckman; Jonathan Petali; Celia Chen; Daniel Amparo; Barbara Turpin; Glenn Morrison; Mark Strynar (Chemosphere, 2023)

Potential for redistribution of post‐moult habitat for Eudyptes penguins in the Southern Ocean under future climate conditions - Cara‐Paige Green; David B. Green; Norman Ratcliffe; David Thompson; Mary‐Anne Lea; Alastair M. M. Baylis; Alexander L. Bond; Charles‐André Bost; Sarah Crofts; Richard J. Cuthbert; Jacob González‐Solís; Kyle W. Morrison; et al. (Global Change Biology, 2023)
Anthropogenic climate change is resulting in spatial redistributions of many species. We assessed the potential effects of climate change on an abundant and widely distributed group of diving birds, Eudyptes penguins, which are the main avian consumers in the Southern Ocean in terms of biomass consumption. Despite their abundance, several of these species have undergone population declines over the past century, potentially due to changing oceanography and prey availability over the important winter months. We used light‐based geolocation tracking data for 485 individuals deployed between 2006 and 2020 across 10 of the major breeding locations for five taxa of Eudyptes penguins. We used boosted regression tree modelling to quantify post‐moult habitat preference for southern rockhopper ( E. chrysocome ), eastern rockhopper ( E. filholi ), northern rockhopper ( E. moseleyi ) and macaroni/royal ( E. chrysolophus and E. schlegeli ) penguins. We then modelled their redistribution under two climate change scenarios, representative concentration pathways RCP4.5 and RCP8.5 (for the end of the century, 2071–2100). As climate forcings differ regionally, we quantified redistribution in the Atlantic, Central Indian, East Indian, West Pacific and East Pacific regions. We found sea surface temperature and sea surface height to be the most important predictors of current habitat for these penguins; physical features that are changing rapidly in the Southern Ocean. Our results indicated that the less severe RCP4.5 would lead to less habitat loss than the more severe RCP8.5. The five taxa of penguin may experience a general poleward redistribution of their preferred habitat, but with contrasting effects in the (i) change in total area of preferred habitat under climate change (ii) according to geographic region and (iii) the species (macaroni/royal vs. rockhopper populations). Our results provide further understanding on the regional impacts and vulnerability of species to climate change.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Ecological and social strategies for managing fisheries using the Resist‐Accept‐Direct (RAD) framework - Abigail J. Lynch; Frank J. Rahel; Doug Limpinsel; Suresh A. Sethi; Augustin C. Engman; David J. Lawrence; Katherine E. Mills; Wendy Morrison; Jay O. Peterson; Mark T. Porath (Fisheries Management and Ecology, 2022)
Fisheries management is a complex task made even more challenging by rapid and unprecedented socioecological transformations associated with climate change. The Resist‐Accept‐Direct (RAD) framework can be a useful tool to support fisheries management in facing the high uncertainty and variability associated with aquatic ecosystem transformations. Here, RAD strategies are presented to address ecological goals for aquatic ecosystems and social goals for fisheries. These strategies are mapped on a controllability matrix which explores the ability to guide a system's behaviour towards a desired state based on ecological responsiveness and societal receptivity to change. Understanding and improving the controllability of aquatic systems and fisheries can help managers to maintain the broadest suite of available RAD management strategies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Phylogeographic structure and historical demography of tarakihi ( Nemadactylus macropterus ) and king tarakihi ( Nemadactylus n.sp.) in New Zealand - Yvan Papa; Alexander G. Halliwell; Mark A. Morrison; Maren Wellenreuther; Peter A. Ritchie (New Zealand Journal of Marine and Freshwater Research, 2022)
Tarakihi ( Nemadactylus macropterus ) is a demersal fish that supports valuable commercial, recreational, and customary fisheries in New Zealand. However, little is known about its stock structure. The population genetic structure, genetic diversity, and demographic history of N. macropterus were investigated using the hypervariable region one of the mitochondrial control region. 370 samples from 14 locations around New Zealand were collected. While weak genetic breaks were detected between Hawke's Bay and East Northland and between the west and east coasts of South Island, no clear genetic structure was detected for the overall New Zealand area (Ф ST = 0.002, P = 0.18), indicative of a panmictic genetic structure. N. macropterus display a high level of genetic diversity and appear to have a historically large and stable population with a long evolutionary history. Bayesian skyline analysis indicates that the historic population has gone through two expansions, likely caused by repeated glacial cycles during the second half of the Pleistocene. The addition of 15 king tarakihi samples ( Nemadactylus n.sp.) collected from the Three Kings Islands showed a clear genetic differentiation between the two morphotypes. These findings can inform the future management of N. macropterus and N . n.sp. to ensure a sustainable harvest.

Climate Change Implications for Tidal Marshes and Food Web Linkages to Estuarine and Coastal Nekton - Denise D. Colombano; Steven Y. Litvin; Shelby L. Ziegler; Scott B. Alford; Ronald Baker; Myriam A. Barbeau; Just Cebrián; Rod M. Connolly; Carolyn A. Currin; Linda A. Deegan; Justin S. Lesser; Charles W. Martin; et al. (Estuaries and Coasts, 2021)
Climate change is altering naturally fluctuating environmental conditions in coastal and estuarine ecosystems across the globe. Departures from long-term averages and ranges of environmental variables are increasingly being observed as directional changes [e.g., rising sea levels, sea surface temperatures (SST)] and less predictable periodic cycles (e.g., Atlantic or Pacific decadal oscillations) and extremes (e.g., coastal flooding, marine heatwaves). Quantifying the short- and long-term impacts of climate change on tidal marsh seascape structure and function for nekton is a critical step toward fisheries conservation and management. The multiple stressor framework provides a promising approach for advancing integrative, cross-disciplinary research on tidal marshes and food web dynamics. It can be used to quantify climate change effects on and interactions between coastal oceans (e.g., SST, ocean currents, waves) and watersheds (e.g., precipitation, river flows), tidal marsh geomorphology (e.g., vegetation structure, elevation capital, sedimentation), and estuarine and coastal nekton (e.g., species distributions, life history adaptations, predator-prey dynamics). However, disentangling the cumulative impacts of multiple interacting stressors on tidal marshes, whether the effects are additive, synergistic, or antagonistic, and the time scales at which they occur, poses a significant research challenge. This perspective highlights the key physical and ecological processes affecting tidal marshes, with an emphasis on the trophic linkages between marsh production and estuarine and coastal nekton, recommended for consideration in future climate change studies. Such studies are urgently needed to understand climate change effects on tidal marshes now and into the future.

Mapping Spatial Distribution and Biomass of Intertidal Ulva Blooms Using Machine Learning and Earth Observation - Sita Karki; Ricardo Bermejo; Robert Wilkes; Michéal Mac Monagail; Eve Daly; Mark Healy; Jenny Hanafin; Alastair McKinstry; Per-Erik Mellander; Owen Fenton; Liam Morrison (Frontiers in Marine Science, 2021)
Graphical Abstract Overall research workflow showing data types, study area, model development and biomass results.

A Phase I Study to Evaluate Two Doses of Wharton’s Jelly-Derived Mesenchymal Stromal Cells for the Treatment of De Novo High-Risk or Steroid-Refractory Acute Graft Versus Host Disease - Rupal P. Soder; Buddhadeb Dawn; Mark L. Weiss; Neil Dunavin; Scott Weir; James Mitchell; Meizhang Li; Leyla Shune; Anurag K. Singh; Siddhartha Ganguly; Marc Morrison; Haitham Abdelhakim; et al. (Stem Cell Reviews and Reports, 2020)

The COVID-19 pandemic: local to global implications as perceived by urban ecologists - Ian Douglas; Mark Champion; Joy Clancy; David Haley; Marcelo Lopes de Souza; Kerry Morrison; Alan Scott; Richard Scott; Miriam Stark; Joanne Tippett; Piotr Tryjanowski; Tim Webb (Socio-Ecological Practice Research, 2020)
The global COVID-19 pandemic is affecting everyone, but in many different ways, stimulating contrasting reactions and responses: opportunities for some, difficulties for many. A simple survey of how individual workers in urban ecology have been coping with COVID-19 constraints found divergent responses to COVID-19 on people’s activities, both within countries and between continents. Many academics felt frustrated at being unable to do fieldwork, but several saw opportunities to change ways of working and review their engagement with the natural world. Some engaging with social groups found new ways of sharing ideas and developing aspirations without face-to-face contact. Practitioners creating and managing urban greenspaces had to devise ways to work and travel while maintaining social distancing. Many feared severe funding impacts from changed local government priorities. Around the world, the COVID-19 pandemic has amplified issues, such as environmental injustice, disaster preparation and food security, that have been endemic in most countries across the global south in modern times. However, developing and sustaining the strong community spirit shown in many places will speed economic recovery and make cities more resilient against future geophysical and people-made disasters. Significantly, top-down responses and one-size-fits-all solutions, however good the modelling on which they are based, are unlikely to succeed without the insights that local knowledge and community understanding can bring. We all will have to look at disaster preparation in a more comprehensive, caring and consistent way in future.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Assessing the Hydrogeomorphic Effects of Environmental Flows using Hydrodynamic Modeling - Angela Gregory; Ryan R. Morrison; Mark Stone (Environmental Management, 2018)

Do elevated blood levels of omega-3 fatty acids modify effects of particulate air pollutants on fibrinogen? - Daniel Croft; Robert Block; Scott J. Cameron; Kristin Evans; Charles J. Lowenstein; Frederick Ling; Wojciech Zareba; Philip K. Hopke; Mark J. Utell; Sally W. Thurston; Kelly Thevenet-Morrison; David Q. Rich (Air Quality, Atmosphere & Health, 2018)

Correction to: Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2018)

Species associations overwhelm abiotic conditions to dictate the structure and function of wood‐decay fungal communities - Daniel S. Maynard; Kristofer R. Covey; Thomas W. Crowther; Noah W. Sokol; Eric W. Morrison; Serita D. Frey; Linda T. A. van Diepen; Mark A. Bradford (Ecology, 2018)
Environmental conditions exert strong controls on the activity of saprotrophic microbes, yet abiotic factors often fail to adequately predict wood decomposition rates across broad spatial scales. Given that species interactions can have significant positive and negative effects on wood‐decay fungal activity, one possibility is that biotic processes serve as the primary controls on community function, with abiotic controls emerging only after species associations are accounted for. Here we explore this hypothesis in a factorial field warming‐ and nitrogen‐addition experiment by examining relationships among wood decomposition rates, fungal activity, and fungal community structure. We show that functional outcomes and community structure are largely unrelated to abiotic conditions, with microsite and plot‐level abiotic variables explaining at most 19% of the total variability in decomposition and fungal activity, and 2% of the variability in richness and evenness. In contrast, taxonomic richness, evenness, and species associations (i.e., co‐occurrence patterns) exhibited strong relationships with community function, accounting for 52% of the variation in decomposition rates and 73% in fungal activity. A greater proportion of positive vs. negative species associations in a community was linked to strong declines in decomposition rates and richness. Evenness emerged as a key mediator between richness and function, with highly even communities exhibiting a positive richness–function relationship and uneven communities exhibiting a negative or null response. These results suggest that community‐assembly processes and species interactions are important controls on the function of wood‐decay fungal communities, ultimately overwhelming substantial differences in abiotic conditions.

Daily land use regression estimated woodsmoke and traffic pollution concentrations and the triggering of ST-elevation myocardial infarction: a case-crossover study - David Q. Rich; Mark J. Utell; Daniel P. Croft; Sally W. Thurston; Kelly Thevenet-Morrison; Kristin A. Evans; Frederick S. Ling; Yilin Tian; Philip K. Hopke (Air Quality, Atmosphere & Health, 2018)

Transcriptome profiles of sunflower reveal the potential role of microsatellites in gene expression divergence - Chathurani Ranathunge; Gregory L. Wheeler; Melody E. Chimahusky; Meaghan M. Kennedy; Jesse I. Morrison; Brian S. Baldwin; Andy D. Perkins; Mark E. Welch (Molecular Ecology, 2018)
The mechanisms by which natural populations generate adaptive genetic variation are not well understood. Some studies propose that microsatellites can function as drivers of adaptive variation. Here, we tested a potentially adaptive role for transcribed microsatellites with natural populations of the common sunflower ( Helianthus annuus L.) by assessing the enrichment of microsatellites in genes that show expression divergence across latitudes. Seeds collected from six populations at two distinct latitudes in Kansas and Oklahoma were planted and grown in a common garden. Morphological measurements from the common garden demonstrated that phenotypic variation among populations is largely explained by underlying genetic variation. An RNA‐Seq experiment was conducted with 96 of the individuals grown in the common garden and differentially expressed (DE) transcripts between the two latitudes were identified. A total number of 825 DE transcripts were identified. DE transcripts and nondifferentially expressed (NDE) transcripts were then scanned for microsatellites. The abundance of different motif lengths and types in both groups were estimated. Our results indicate that DE transcripts are significantly enriched with mononucleotide repeats and significantly depauperate in trinucleotide repeats. Further, the standardized mononucleotide repeat motif A and dinucleotide repeat motif AG were significantly enriched within DE transcripts while motif types, C, AT, ACC and AAC in DE transcripts, are significantly differentiated in microsatellite tract length between the two latitudes. The tract length differentiation at specific microsatellite motif types across latitudes and their enrichment within DE transcripts indicate a potential functional role for transcribed microsatellites in gene expression divergence in sunflower.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2016)

Five ways to support interdisciplinary work before tenure - Melinda Harm Benson; Christopher D. Lippitt; Ryan Morrison; Barbara Cosens; Jan Boll; Brian C. Chaffin; Alexander K. Fremier; Robert Heinse; Derek Kauneckis; Timothy E. Link; Caroline E. Scruggs; Mark Stone; et al. (Journal of Environmental Studies and Sciences, 2016)

High connectivity in a long-lived high-Arctic seabird, the ivory gull Pagophila eburnea - Glenn Yannic; Jonathan M. Yearsley; Roberto Sermier; Christophe Dufresnes; Olivier Gilg; Adrian Aebischer; Maria V. Gavrilo; Hallvard Strøm; Mark L. Mallory; R. I. Guy Morrison; H. Grant Gilchrist; Thomas Broquet (Polar Biology, 2016)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Using a Gas-Phase Tracer Test to Characterize the Impact of Landfill Gas Generation on Advective-Dispersive Transport of VOCs in the Vadose Zone - Gregg R. Monger; Candice Morrison Duncan; Mark L. Brusseau (Water, Air, & Soil Pollution, 2014)

Modeling and simulation for medical product development and evaluation: highlights from the FDA-C-Path-ISOP 2013 workshop - Klaus Romero; Vikram Sinha; Sandra Allerheiligen; Meindert Danhof; Jose Pinheiro; Naomi Kruhlak; Yaning Wang; Sue-Jane Wang; John-Michael Sauer; J. F. Marier; Brian Corrigan; James Rogers; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Determination of Chlorinated Solvent Sorption by Porous Material—Application to Trichloroethene Vapor on Cement Mortar - Marion Musielak; Mark L. Brusseau; Manuel Marcoux; Candice Morrison; Michel Quintard (Transport in Porous Media, 2014)

The influence of habitat structure on juvenile fish in a New Zealand estuary - Darren M. Parsons; Mark A. Morrison; Simon F. Thrush; Crispin Middleton; Matt Smith; Keren T. Spong; Dane Buckthought (Marine Ecology, 2013)
Estuarine and sheltered coastal habitats that contain physical structure are potentially important nurseries for juvenile fish. Many of these structured habitats, however, are potentially vulnerable to stressors such as elevated turbidity. Quantifying the benefits that structured habitats provide to juvenile fish may therefore be an important step in the management process. We investigated the value of structured habitat for juvenile fishes in northeastern New Zealand, using artificial seagrass units ( ASU s) with varying blade density. ASU s were predominantly settled by juvenile snapper ( Pagrus auratus ) and spotty ( Notolabrus celidotus ). The density of both snapper and spotty was greatest on ASU s with the highest blade density. For snapper, a gradient in abundance was present (with higher abundance closer to the harbour mouth), suggesting either a gradient in the supply of recruits or a potential recruitment shadow effect. The size distribution of juvenile snapper (12–70 mm fork length) was very similar on both sampling trips, despite the 2‐month interim period, suggesting an ontogenetic habitat shift dependent on size. The condition of juvenile snapper from ASU s with the highest blade density was also greater than the other ASU treatments. Overall, these results provide new empirical evidence that habitats with physical structure within shallow estuarine systems are important to early stage juvenile fishes such as snapper, and indicate that the location‐specific context of that habitat is also likely important.

Are lower‐latitude plants better defended? Palatability of freshwater macrophytes - Wendy E. Morrison; Mark E. Hay (Ecology, 2012)
Increased herbivory at lower latitudes is hypothesized to select for more effective plant defenses. Feeding assays with seaweeds and salt marsh plants support this hypothesis, with low‐latitude plants experiencing greater damage in the field and being less palatable than higher‐latitude plants. We tested this hypothesis for freshwater macrophytes because they offered an independent plant lineage and habitat type for testing this general hypothesis and because the patchiness of consumer occupancy across isolated water bodies might produce local variance in herbivory that would override geographic variance and produce different results for this habitat type. When we fed eight congeneric pairs of live plants from four sites in Indiana vs. four sites in South Florida (∼215 and 0 frost days/yr respectively) to three species of crayfishes and one species of snail, three of the four herbivores significantly preferred high‐latitude to low‐latitude plants. For two crayfishes that differed in feeding on live plants (one favoring high‐latitude plants and one not), we retested feeding using foods composed of freeze‐dried and finely ground plants, thus removing structural characteristics while retaining most chemical/nutritional traits. In this assay, both herbivores strongly preferred high‐latitude plants, suggesting that lower‐latitude plants had been selected for more deterrent chemical traits. When we collected 22 pairs of congeneric plants from 9 sites throughout Indiana vs. 13 sites in Central Florida (∼215 and ∼95 frost days/yr respectively) and tested these in feeding assays with three crayfishes using dried, ground, and reconstituted plant material, we found a significant effect of latitude for only one of three species of herbivore. Overall, our results suggest a preference for high‐latitude plants, but the strength of this relationship varied considerably across small scales of latitude that differed considerably in numbers of frost‐free days. The difference in results suggests that large changes in frost frequency over small spatial scales may affect selection for plant defenses, that local variance in herbivory overrode differential selection at geographic scales, or that these possibilities interact when durations of cold weather periodically exclude herbivores from shallower habitats, producing heterogeneous selection for defenses at small spatial scales.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Phylogenetic diversity of bacterial communities in bovine rumen as affected by diets and microenvironments - Minseok Kim; Mark Morrison; Zhongtang Yu (Folia Microbiologica, 2011)

Feeding and growth of native, invasive and non-invasive alien apple snails (Ampullariidae) in the United States: Invasives eat more and grow more - Wendy E. Morrison; Mark E. Hay (Biological Invasions, 2011)

Induced chemical defenses in a freshwater macrophyte suppress herbivore fitness and the growth of associated microbes - Wendy E. Morrison; Mark E. Hay (Oecologia, 2011)

Willingness to Pay and Willingness to Accept Compensation for Changes in Urban Water Customer Service Standards - Darla Hatton MacDonald; Mark D. Morrison; Mary B. Barnes (Water Resources Management, 2010)

Ironing out the wrinkles in the rare biosphere through improved OTU clustering - Susan M. Huse; David Mark Welch; Hilary G. Morrison; Mitchell L. Sogin (Environmental Microbiology, 2010)
Summary Deep sequencing of PCR amplicon libraries facilitates the detection of low‐abundance populations in environmental DNA surveys of complex microbial communities. At the same time, deep sequencing can lead to overestimates of microbial diversity through the generation of low‐frequency, error‐prone reads. Even with sequencing error rates below 0.005 per nucleotide position, the common method of generating operational taxonomic units (OTUs) by multiple sequence alignment and complete‐linkage clustering significantly increases the number of predicted OTUs and inflates richness estimates. We show that a 2% single‐linkage preclustering methodology followed by an average‐linkage clustering based on pairwise alignments more accurately predicts expected OTUs in both single and pooled template preparations of known taxonomic composition. This new clustering method can reduce the OTU richness in environmental samples by as much as 30–60% but does not reduce the fraction of OTUs in long‐tailed rank abundance curves that defines the rare biosphere.

Patient preferences and National Health Service costs: a cost-consequences analysis of cancer genetic services - Gethin L. Griffith; Rhiannon Tudor Edwards; J. Mark G. Williams; Jonathon Gray; Val Morrison; Clare Wilkinson; Jim Turner; Barbara France; Paul Bennett (Familial Cancer, 2009)

Risks of shifting baselines highlighted by anecdotal accounts of New Zealand's snapper ( Pagrus auratus ) fishery - Darren M. Parsons; Mark A. Morrison; Alison B. MacDiarmid; Bruce Stirling; Phillip Cleaver; Ian W.G. Smith; Maria Butcher (New Zealand Journal of Marine and Freshwater Research, 2009)
Anecdotal data sources may constitute an important component of the information available about an exploited species, as record keeping may not have occurred until after exploitation began. Here, we aimed to fill any gaps in the exploitative history of the sparid snapper ( Pagrus auratus ), using social and historical research methods. Social research consisted of interviews with recreational fishers, focusing on the most and largest snapper they had caught. In addition, the diary‐logs of two recreational fishers were analysed. Historical research consisted of investigation of old books, photos, archives and unpublished sources unconventional to fishery science. Interviews with fishers demonstrated no or weak trends in snapper abundance or size, and were likely impeded by a lack of ability to detect change in a fish stock that may still be considered abundant. The fishers’ perception of change, however, largely reflected recent experiences (last c. 10 years), when biomass is understood to have increased, and mostly did not consider experiences before the 1980s. Alternatively, diary‐logs of fisher catch rates produced a pattern that matched formal stock assessments of snapper biomass, suggesting declines in abundance up until the 1990s and an increase in biomass after that time. Historical research, although more qualitative, had the ability to investigate periods where formal records were not kept and described a fishery vastly different from the current one. Snapper were easily caught, in great abundance and in unusual locations. Localised depletion of snapper was first noticed in the early 20th century, despite spectacular catches of snapper occurring after that time. Snapper behaviour was also likely different, with visual sightings of snapper by onlookers a common occurrence. Although predictions from stock assessment models are consistent with that of the anecdotes listed here (i.e., high biomass in the past), these anecdotes are valuable as they explain lost biomass in a perspective meaningful to all. This perspective may be valuable for managers trying to consider the non‐financial value of a shared fishery but, if unrecognised, represents a shifting baseline.

Addition of individual chromosomes of maize inbreds B73 and Mo17 to oat cultivars Starter and Sun II: maize chromosome retention, transmission, and plant phenotype - Howard W. Rines; Ronald L. Phillips; Ralf G. Kynast; Ron J. Okagaki; Mark W. Galatowitsch; Paul A. Huettl; Adrian O. Stec; Morrison S. Jacobs; Jayanti Suresh; Hedera L. Porter; Matthew D. Walch; Candida B. Cabral (Theoretical and Applied Genetics, 2009)

An Efficient RNA Extraction Method for Estimating Gut Microbial Diversity by Polymerase Chain Reaction - Seungha Kang; Stuart E. Denman; Mark Morrison; Zhongtang Yu; Chris S. McSweeney (Current Microbiology, 2009)

Effect of PCR amplicon size on assessments of clone library microbial diversity and community structure - Julie A. Huber; Hilary G. Morrison; Susan M. Huse; Phillip R. Neal; Mitchell L. Sogin; David B. Mark Welch (Environmental Microbiology, 2009)
Summary PCR‐based surveys of microbial communities commonly use regions of the small‐subunit ribosomal RNA (SSU rRNA) gene to determine taxonomic membership and estimate total diversity. Here we show that the length of the target amplicon has a significant effect on assessments of microbial richness and community membership. Using operational taxonomic unit (OTU)‐ and taxonomy‐based tools, we compared the V6 hypervariable region of the bacterial SSU rRNA gene of three amplicon libraries of c. 100, 400 and 1000 base pairs (bp) from each of two hydrothermal vent fluid samples. We found that the smallest amplicon libraries contained more unique sequences, higher diversity estimates and a different community structure than the other two libraries from each sample. We hypothesize that a combination of polymerase dissociation, cloning bias and mispriming due to secondary structure accounts for the differences. While this relationship is not linear, it is clear that the smallest amplicon libraries contained more different types of sequences, and accordingly, more diverse members of the community. Because divergent and lower abundant taxa can be more readily detected with smaller amplicons, they may provide better assessments of total community diversity and taxonomic membership than longer amplicons in molecular studies of microbial communities.

A genetic test for recruitment enhancement in Chesapeake Bay oysters, Crassostrea virginica, after population supplementation with a disease tolerant strain - Matthew P. Hare; Standish K. Allen; Paulette Bloomer; Mark D. Camara; Ryan B. Carnegie; Jenna Murfree; Mark Luckenbach; Donald Meritt; Cheryl Morrison; Kennedy Paynter; Kimberly S. Reece; Colin G. Rose (Conservation Genetics, 2006)

Improved serial analysis of V1 ribosomal sequence tags (SARST‐V1) provides a rapid, comprehensive, sequence‐based characterization of bacterial diversity and community composition - Zhongtang Yu; Marie Yu; Mark Morrison (Environmental Microbiology, 2006)
Summary Serial analysis of ribosomal sequence tags (SARST) is a recently developed technology that can generate large 16S rRNA gene ( rrs ) sequence data sets from microbiomes, but there are numerous enzymatic and purification steps required to construct the ribosomal sequence tag (RST) clone libraries. We report here an improved SARST method, which still targets the V1 hypervariable region of rrs genes, but reduces the number of enzymes, oligonucleotides, reagents, and technical steps needed to produce the RST clone libraries. The new method, hereafter referred to as SARST‐V1, was used to examine the eubacterial diversity present in community DNA recovered from the microbiome resident in the ovine rumen. The 190 sequenced clones contained 1055 RSTs and no less than 236 unique phylotypes (based on ≥ 95% sequence identity) that were assigned to eight different eubacterial phyla. Rarefaction and monomolecular curve analyses predicted that the complete RST clone library contains 99% of the 353 unique phylotypes predicted to exist in this microbiome. When compared with ribosomal intergenic spacer analysis (RISA) of the same community DNA sample, as well as a compilation of nine previously published conventional rrs clone libraries prepared from the same type of samples, the RST clone library provided a more comprehensive characterization of the eubacterial diversity present in rumen microbiomes. As such, SARST‐V1 should be a useful tool applicable to comprehensive examination of diversity and composition in microbiomes and offers an affordable, sequence‐based method for diversity analysis.

Novel microbial diversity adherent to plant biomass in the herbivore gastrointestinal tract, as revealed by ribosomal intergenic spacer analysis and rrs gene sequencing - Ross Larue; Zhongtang Yu; Victoria A. Parisi; Adrian R. Egan; Mark Morrison (Environmental Microbiology, 2005)
Summary It is well recognized that a dynamic biofilm develops upon plant biomass in the herbivore gastrointestinal tract, but this component of the microbiome has not previously been specifically sampled, or directly compared with the biodiversity present in the planktonic fraction of digesta. In this study, the digesta collected from four sheep fed two different diets was separated into three fractions: the planktonic phase, and the microbial populations either weakly or tightly adherent to plant biomass. The community DNA prepared from each fraction was then subjected to both ribosomal intergenic spacer analysis (RISA) and denaturing gradient gel electrophoresis (DGGE). Both types of analysis showed that dietary factors influence community structure, and that the adherent fractions produced more complex profiles. The RIS‐clone libraries prepared from the planktonic and adherent populations were then subjected to restriction fragment length polymorphism (RFLP) and DNA sequence analyses, which resulted in a far greater degree of discrimination among the fractions. Although many of the sequenced clones from the adherent populations were assigned to various clusters within the low G+C Gram‐positive bacteria, the clone libraries from animals consuming an all‐grass diet were largely comprised of novel lineages of Clostridium , while in animals consuming the starch‐containing diet, Selenomonas and Ruminococcus spp. were the dominant low G+C Gram‐positive bacteria. Additionally, the libraries from hay‐fed animals also contained clones most similar to asaccharolytic Clostridia, and other Gram‐positive bacteria that specialize in the transformation of plant phenolic compounds and the formation of cinnamic, phenylacetic and phenylpropionic acids. These results reveal, for the first time, the phylogeny of adherent subpopulations that specialize in the transformation of plant lignins and other secondary compounds, which potentiate polysaccharide hydrolysis by other members of the biofilm.

Strain‐specific genomic regions of Ruminococcus flavefaciens FD‐1 as revealed by combinatorial random‐phase genome sequencing and suppressive subtractive hybridization - Dionysios A. Antonopoulos; Karen E. Nelson; Mark Morrison; Bryan A. White (Environmental Microbiology, 2004)
Summary Two closely related strains of the Gram‐positive, cellulolytic ruminal bacterium Ruminococcus flavefaciens were compared at the genomic level by suppressive subtractive hybridization. The two strains investigated in this study differ by 1.94% in their respective 16S rDNA genes. Three hundred and eighty‐four PCR‐amplified products were cloned and then screened for their strain identity by dot blot hybridization. Based on redundancy percentages of the clones sequenced, 9.5% of the genome of the R. flavefaciens FD‐1 strain is not present in the JM1 strain. The majority of identities of individual cloned subtracted products (642 bp average length) bore no relation to deposited sequences in GenBank (42% of the subtracted library), whereas of those with putative assigned functions 7% are loosely associated with fibre‐degradation, 6% with insertion elements, transposons and phage‐like ORFs, 5% with cell membrane associated proteins and 3% with signal transduction. Subtracted sequences were then supplemented with the draft (2 × coverage) genome sequence of R. flavefaciens FD‐1 to indicate potential regions of rearrangement within the genome, including a novel insertion sequence.

Characterisation of a novel class of polyamine-based neuroprotective compounds - Ashley K. Pringle; Barclay Morrison; Mark Bradley; Fausto Iannotti; Lars E. Sundstrom (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Invasion of the Asian goby, Acentrogobius pflaumii , into New Zealand, with new locality records of the introduced bridled goby, Arenigobius bifrenatus - Malcolm P. Francis; Cameron Walsh; Mark A. Morrison; Crispin Middleton (New Zealand Journal of Marine and Freshwater Research, 2003)
The Asian goby, Acentrogobius pflaumii (Bleeker, 1853), is reported from New Zealand waters for the first time. It was collected by beach seine in 2001–02 from muddy substrata in the upper reaches of the Waitemata and Whangapoua Harbours. We suggest that A. pflaumii has been introduced to New Zealand, probably in ship ballast water. It may have arrived directly from its native range in the north‐west Pacific Ocean, or indirectly via Australia, which it invaded before 1996. The Australian bridled goby, Arenigobius bifrenatus (Kner, 1865), which is also thought to have invaded New Zealand via ballast water, is here recorded from three new locations, extending its known New Zealand range to five different harbours spanning c. 150 km of coastline. This species is more widespread than previously thought and appears well established. Both gobies have been found only on the east coast of the North Island.

Identification and characterization of a novel murine beta-defensin-related gene - Gillian M. Morrison; Mark Rolfe; Fiona M. Kilanowski; Sally H. Cross; Julia R. Dorin (Mammalian Genome, 2002)